Ocean Literacy to Promote Sustainable Development Goals and Agenda 2030 in Coastal Communities - José Carlos Ferreira; Lia Vasconcelos; Renato Monteiro; Flávia Zurga Silva; Cláudio Macedo Duarte; Filipa Ferreira (MDPI AG, 2021)
Ambassadors for Biodiversity (EmBio) is an ocean literacy research project that contributes to the improvement of literacy on marine and coastal biodiversity, namely encompassing the areas covered by the Natura 2000 Network, by promoting coastal and oceanic resources conservation and natural and cultural values preservation of the Portuguese western Atlantic coast. This project directly promotes the achievement of the Sustainable Development Goals (SDGs) and the implementation of 2030 Agenda developed by the United Nations and adopted by most countries in the world, which define the priorities and aspirations for global sustainable development until the year of 2030, mobilizing a world-wide effort to meet a common set of goals and objectives. This paper contributes to understanding how ocean literacy, and specifically the EmBio research project, fits into the international agenda for sustainable development and the SDGs and its targets. Through an analysis and a comparison between the project EmBio and the SDGs, it was possible to identify connections on 11 out of 17 goals and 31 out of 169 targets, with a special emphasis on the SDG 14-Life Below Water. The results highlight the relevance of this project and, especially, ocean literacy for the accomplishment of the SDGs.